Modified Film Form in Reference to Contextual 3-D Filmmaking: Challenging the Monopoly of Film Form and Dissemination of Knowledge in Indonesia - Tunggul Banjaransari (International Journal of Visual and Performing Arts, 2019)
The variety of films distributed in Indonesia are homogenous, which profoundly impacts the dissemination of knowledge generated by the movie. Since the information exposed to the public derived from one single source, it is highly potential to politicize the distribution of society’s collective knowledge — for instance, the arrangement on film circulation. Indonesian Censorship Institute does not only authorized the quantity of the film circulated in the country but also regulates the quality of the movie itself. Films that contain any ideological deviation, moral standards digression, and disobedience to the State will surely be banned. Inevitably, the flow of capital for filmmaking shall follow the State’s standard of circulation. The flourishment of the Indonesian community-based independent film screenings network simultaneously provides an alternative source of information to society. Such knowledge—regarded by the State as the Other—is vital since the enormous scope of knowledge is inaccessible as a result of the State’s limitation. The film communities dedicate alternative screenings as a space for the audience to explore various kinds of films with different knowledge. The researcher experimented with combining the situation of the society constrained by the State with the adaptation of 3-D filmmaking. The adjustment is manifested in the utilization of layered-narrative as an effort to illustrate the role of information obtained from various sources. The experiment is expected to encourage the audience to gain knowledge as if they were putting the pieces of the film scenes into a puzzle.